1987
DOI: 10.1007/bf01418834
|View full text |Cite
|
Sign up to set email alerts
|

Syringosubarachnoid shunt for treatment of syringomyelia

Abstract: The experiences with a series of 9 patients with syringomyelia treated by syringosubarachnoid shunt (SSS) are presented. All of the cases were evaluated by myelography, CT scan or MNR. The cases showed satisfactory results which consisted in stabilization of the symptoms (55%) or clinical improvement (44%). These results should be continuously evaluated, due to the short follow-up period and to the variable natural history of the illness. Treatment by SSS is a technique of low morbidity. It is recommended for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…One patient developed postoperative meningitis and an intramedullary abscess at the tip of the shunt catheter despite adequate antibiotic treatment. Therefore, we are unable to substantiate reports which recommend shunting as the method of choice in Chiari I malformation with syringomyelia [31,35,61].…”
Section: Results For Shunting Of the Syrinxcontrasting
confidence: 56%
“…One patient developed postoperative meningitis and an intramedullary abscess at the tip of the shunt catheter despite adequate antibiotic treatment. Therefore, we are unable to substantiate reports which recommend shunting as the method of choice in Chiari I malformation with syringomyelia [31,35,61].…”
Section: Results For Shunting Of the Syrinxcontrasting
confidence: 56%
“…However, with recent progress in microsurgical technique subarachnoid shunt has been again receiving syringoattention [21][22][23]. In this report, the authors stress that the syringo-subarachnoid shunt is effective as a surgical procedure for syringomyelia associated with Chiari malformation.…”
Section: Introductionmentioning
confidence: 79%
“…Longne [17] reported that simple decompression of the posterior fossa should give results similar to the surgical procedure involving the syrinx. Some authors [22,5] think that a more rational approach would be an extramedullary shunt since the syrinx comes under pulsatile pressure from extraspinal structures during coughing and laughing, and increasing pressure from abdominal tension. Some authors [22,5] think that a more rational approach would be an extramedullary shunt since the syrinx comes under pulsatile pressure from extraspinal structures during coughing and laughing, and increasing pressure from abdominal tension.…”
Section: Discussionmentioning
confidence: 99%